Property as an investment - Mohd. Ali, Hishamuddin; Lee, Janice Yim Mei (Fakulti Kejuruteraan Dan Sains Geoinformasi, 2007)
table of content preface, acknowledgement, chapter one: introduction to investment, what is an investment?, investment definitions, principles of investment, types of This book contains several chapters like investment risks, chapter two: investment media and objectives, types of investment media, investment qualities, objectives of investment, investor profile and typical investments, chapter three: direct property investment, property asset characteristics, property market characteristics, property as investment class, advantages and disadvantages of property investment, costs involved in direct property investment, property investment process, chapter four: indirect property investment, property company shares, real estate investment trusts (REITS), real estate mortgages securities, appendices, references.